The Name of Jesus in Matthew - O’ Collins, Gerald (Asian Horizons, 2024)
The Easter narrative of Matthew 28, unlike those of Luke and John, does not refer to the Risen One as Lord. Unlike Luke 24, it does not name him as the Son of Man. While once naming him as Son (in the baptismal formula), Matthew 28 five times calls him Jesus. This is the personal name which the evangelist explained in his opening chapter, the name which held together the teaching, healing, and other activity of Jesus’ ministry, and which unifies the final Easter chapter. Up to Chapter 27, Matthew has cited the Scriptures to illuminate the ministry of Jesus. Now the Scriptures fall silent; the risen Jesus speaks for himself, the divine Emmanuel who accompanies the Church on her universal mission.